UTILIZATION OF NATURAL RESOURCES OF TILAPIA FISH BONES FOR FOOD SECURITY IN WONOGIRI REGENCY - Pambudi, Ilham Galih; Saputro, Uji; Mulyani, Sri; Wiyan, Shalima Azahra Putrina; Majidah, Nirmala Nurul (International Conference On Social Science Education, 2024)
This research is motivated by the fact that the Wonogiri Regency area has a variety of natural riches that have not been utilized optimally by the surrounding community, including the abundant tilapia fish from the Gajah Mungkur reservoir. So far, the flesh of the tilapia fish has only been used for consumption, not the bones, so this research examines the use of the tilapia bones. The research method used is experimentation through several stage processes. This research was carried out to develop innovations in the use of tilapia fish bones by extracting tilapia fish bones into powder modifying it with tapioca flour, and combining it with vegetables into a product in the form of instant noodles with the name MIGATISAY. Data were collected using a questionnaire distributed to residents of SMA Negeri 2 Wonogiri and several people from the community randomly as respondents by answering the questionnaire questions that had been provided. The research results obtained show that noodles from tilapia fish bones have several nutritional contents based on laboratory tests that we conducted at USB Laboratory. It is known that the contents contained in it include carbohydrates consisting of 78.23%, protein content 5.10%, fat 2.25%, ash content 5.07%, and water content 9.35%. The test results from the Wonogiri Health Service showed that the examination data for the mixture of preservatives and dyes was negative.